The effects of Ficus auriculata (fig) on cell cycle profile and apoptosis activity of Human lung adenocarcinoma cells, A549 - Jamil, Elyna Fatini; Abdul Ghani, Radiah (2016)
Ficus auriculata (fig) has an immense value of benefits with regards to their medicinal and therapeutic properties. (Fig) has been long used in traditional folk medicine, Traditional Chinese Medicine (TCM) and Ayurveda. Many scientific researches have proven the usage of this natural medicine in in vitro and in vivo studies, where anti-cancer is among of its recognized properties. To acquire further details on how F.auriculata (fig) inhibited cancer growth, we investigated the effects of its exposure on cell cycle profile. Subsequently we determined the type of cell death and the mechanism it induced using flow cytometer. Human lung adenocarcinoma cell line A549 was selected as the model of this study. Results indicated significant decreased of A549 cells in G0/G1 and concurrent accumulation of cells in G2/M phase. Cell death analysis revealed significant late apoptosis induced by F.auriculata (fig) via caspase independent pathway. Therefore, we concluded that F.auriculata (fig) is one of the promising natural medicines that can be used as cancer preventive strategy, as a result from its effects against cell cycle profile and apoptosis via caspase independent pathway.